2022
DOI: 10.1111/ejh.13826
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing antibody responses against SARS‐CoV‐2 in patients with plasma cell disorders who are on active treatment after two doses of mRNA vaccination

Abstract: Many patients with plasma cell disorder (PCD) on active treatment with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) require hospitalization, with an increased mortality rate over healthy adults. The FDA approved two mRNA vaccines against SARS‐CoV‐2: BNT162b2 and mRNA‐1273. To assess the efficacy of vaccination in patients with PCD, retrospectively, we identified all patients on active treatment. A total of 149 patients were included. Neutralizing antibodies (NAbs) levels against SARS‐CoV‐2 adeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…But on the other hand, there are, as yet, no clear guidelines for antimicrobial prophylaxis therapy in cases of RRMM. Although we did not observe a high incidence of coronavirus disease 2019 (COVID-19) infection in our patient population, daratumumab has been reported to have lower neutralizing antibodies after vaccination and thus higher risk of infection [ 24 ]. Immunoglobulin replacement therapy has not improved outcomes and is associated with increased risk of thrombosis and renal injury [ 25 ].…”
Section: Discussionmentioning
confidence: 70%
“…But on the other hand, there are, as yet, no clear guidelines for antimicrobial prophylaxis therapy in cases of RRMM. Although we did not observe a high incidence of coronavirus disease 2019 (COVID-19) infection in our patient population, daratumumab has been reported to have lower neutralizing antibodies after vaccination and thus higher risk of infection [ 24 ]. Immunoglobulin replacement therapy has not improved outcomes and is associated with increased risk of thrombosis and renal injury [ 25 ].…”
Section: Discussionmentioning
confidence: 70%
“…Studies have also reported that older age, lymphopenia and active treatment with BCMA-targeting agents are associated with low rates of antibody response following prime two-dose COVID-19 vaccination [ 71 , 72 , 74 , 76 78 , 81 , 86 , 88 , 89 , 94 , 96 ]. Recent ASCT does not seem to impair humoral responses to COVID-19 vaccination, thus most SCT-center recommend re-boosters post ASCT [ 84 , 100 , 107 , 108 ].…”
Section: Methodsmentioning
confidence: 99%
“…In patients with MM, SARS-CoV-2 infection has been associated with a severe clinical course and high mortality rates, due to the concomitant disease- and treatment-related immunosuppression [ 1 ]. Furthermore, MM patients respond poorly to vaccination despite adequate immunization, especially those on treatment with anti-CD38 or anti-BCMA therapies [ 2 , 3 , 4 , 5 ]. Thus, MM patients are at a higher risk for breakthrough infection compared with noncancer patients or patients with solid tumor, and supportive measures along with prophylactic use of monoclonal antibodies against SARS-CoV-2 are needed [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%